Buy now pay later and university students: the tempting convenience - Ishak, Rosbi (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
If you have ever seen the “Pay in 3” or “Pay Later” option at checkout when buying something online, you have already met the concept of Buy Now, Pay Later — or BNPL. It is fast, easy, and honestly quite tempting. As university students juggling limited budgets, many of us are drawn to anything that offers a little breathing room with money. BNPL seems like the perfect solution: get what you need (or want) now, and pay for it later — interest-free. What is Buy Now, Pay Later? Buy Now, Pay Later allow you split the cost of a purchase into a few smaller payments, usually over several weeks or months. You get the product right away, and as long as you pay on time, you typically will not pay any interest. Popular apps like Atome, Shopee PayLater, and ShopBack PayLater are everywhere now, and the whole process is fast — sometimes just a few clicks. You do not even need a credit card (Statista Research Department, 2024). That is part of the reason it is so attractive to students.